When Silence Speaks: Exploring English-Speaking Skills of Introverted Learners - Azis, Mira Aristi; Putri, Andi Mega Januarti; Fajriani, Fajriani (Universitas Sulawesi Barat, 2025)
This study explores the English-speaking challenges and coping strategies of introverted learners in an Indonesian senior high school EFL context. Using a qualitative descriptive design, ten eleventh-grade students at SMAN 1 Wonomulyo were purposively selected based on a personality assessment identifying them as introverted. Data were collected through classroom observations, semi-structured interviews, a speaking test, and questionnaires. The findings reveal that introverted students commonly face difficulties in speaking tasks due to fear of judgment, discomfort in group settings, hesitation in expressing ideas, and slow verbal processing. These psychological and linguistic barriers significantly affect their classroom participation and oral performance. However, the students also demonstrated adaptive strategies such as memorizing prepared texts, managing their preparation time effectively, and responding positively to motivational support from teachers and peers. Additionally, they expressed a preference for game-based and relaxed learning environments that reduce performance pressure. The study highlights the need for inclusive and responsive language teaching practices that cater to diverse learner personalities. It contributes to the growing understanding of how personality traits influence language learning and provides practical implications for fostering speaking confidence among introverted learners in EFL classrooms.